2000
DOI: 10.1677/joe.0.1640255
|View full text |Cite
|
Sign up to set email alerts
|

ACTH treatment disrupts ovarian IGF-I and steroid hormone production

Abstract: Hyper-adrenal activity and increased glucocorticoid hormone release are associated with disruptions in reproductive function and adverse effects on the ovary. The aim of this investigation was to determine whether elevated glucocorticoid hormone levels can influence ovarian IGF-I synthesis and action in vivo. To elevate endogenous glucocorticoid levels, gilts were treated with ACTH during the luteal phase of the oestrous cycle (days 9-13) while the control group received saline. The gilts were subsequently ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…ACTH stimulates the conversion of cholesterol to pregnenolone in the adrenal cortex (Simpson and Waterman, 1988), which is rapidly converted to progesterone, 17αhydroxyprogesterone and androstenedione by the enzymes 3β-HSD and 17α-hydroxylase/17,20-lyase (cytochrome P450c17) respectively. Although long-term administration of ACTH seems to disrupt ovarian steroidogenesis (Viveiros and Liptrap, 2000), the short-term administration used in this study may not have affected any of the ovarian functions.…”
Section: Discussionmentioning
confidence: 83%
“…ACTH stimulates the conversion of cholesterol to pregnenolone in the adrenal cortex (Simpson and Waterman, 1988), which is rapidly converted to progesterone, 17αhydroxyprogesterone and androstenedione by the enzymes 3β-HSD and 17α-hydroxylase/17,20-lyase (cytochrome P450c17) respectively. Although long-term administration of ACTH seems to disrupt ovarian steroidogenesis (Viveiros and Liptrap, 2000), the short-term administration used in this study may not have affected any of the ovarian functions.…”
Section: Discussionmentioning
confidence: 83%
“…Using cultures of rat osteoblasts, Delany and Canalis 44 demonstrated that cortisol decreased Igf1 mRNA by approximately 50% through decreasing gene transcription. Furthermore, studies in the pig have shown that increased glucorticoid concentrations can disrupt ovarian IGF1 synthesis and IGF action both in vitro 45 and in vivo 46 . In rats, both acute and chronic corticosterone administration significantly decreased Bdnf mRNA and protein in the hippocampus 47 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids were found to enhance FSH-stimulated progesterone synthesis in cultured granulosa cells of rats and cattle [77][78][79] and to suppress P450 aromatase activity and decrease the number of LH receptors in rats [78,80], cattle [79], and pigs [81]. Furthermore, porcine studies have demonstrated that increased glucocorticoid concentrations can disrupt ovarian IGF1 synthesis and IGF action both in vitro and in vivo [82,83]. On the other hand, glucocorticoids were found to promote androgen production by cultured thecal cells in cattle [84].…”
Section: Liang Et Almentioning
confidence: 99%